ملامح التداولية في كتاب الرسالة للإمام الشافعي - ميسه, محمد الصغير (University of El-oued, 2020)
تناول المقال إشكالية لسانية هامة، الغرض منها الكشف عن ملامح التداولية في كتاب"الرسالة" للإمام الشافعي بوصفه أول كتاب ألِّف في أصول الفقه، فبعد التعريف اللغوي والاصطلاحي بالاتجاه اللساني التداولي، تمّ التطرق إلى مظاهر التداولية في كتاب "الرسالة" ومقارنتها بما توصلت إليه الدراسات اللسانية الحديثة؛ نذكر منها: الاقتضاء والقصدية والسياق والحِجاج وصيغ الخبر والإنشاء وصلتها بأفعال الكلام، ليُختم المقال برصد جملة من النتائج تؤكد في مجملها على وجود بذور للتداولية في هذا المؤلَّف الثمين. Summary: The article dealt with an important linguistic problem; whose purpose is to reveal the features of deliberativeism in the book "The Message" by Imam Al-Shafi’i as the first book written in the OussoulElFIkh.After the linguistic and idiomatic definition of the linguistic approach to deliberation, aspects of deliberation were discussed in the book "The Rissala" and comparing it with the Modern and linguisticswe mentioned: necessity, intentionality, context, proofs, formulas the declarative and nondeclarative forms and their connection to verbal acts, toend the article by observing a set of results that confirm in its entirety the existence of seeds for deliberation in this precious author.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج03. ع.01. جامعة الوادي
Keywords: تداولية، اقتضاء، قصدية، سياق، حِجاج; deliberative, necessity, intentionality, context, proofs.